A comparative study of the intermittent long and short training and their impact on the power of the speed of the football players - mansouri, Abdallah (sports creativity, 2025)
The study aimed at identifying the contribution of both long intermittent training and the short intermittent training in developing the power of the speed of the football players, in order to study the extent of the effectiveness of the two proposed programs, we have conducted a study at the amateur championship, which includes 400 footballers for the 2019/2020 sports season. The sample included 20 soccer players of Amal Chelghoum laid and 20 soccer players of Hilal Chelghoum laid, were have selected from the research community in a deliberate manner, in this study, we have adopted the experimental method by carrying out the tribal test on 10-11 / 2019, followed by the implementation of the two training programs designed by the researcher and then completed with the post-test on 26-27 october 2019. In analyzing the results, we have concluded that the short intermittent training is more effective in